(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There is an upsurge in nationalism throughout the globe. Number of people are advocating for domestic and regional products have increased over the time. India is indifferent towards this. Buy domestic campaigns, which were in aggressive forms during the time of independence have returned with lesser intensity. Those people leading anti-globalization protests justify their protests citing rising inequality, Income disparity, Unemployment, and exit of many domestic firms from market unable to compete with global giants.Nationalism has always been a tool of marketing in India. Patriotism is being used as a brand positioning strategy for Indian consumers. It can be seen that companies which are foreign based or are largely funded by foreign corporates are also adopting such brand positioning strategies. Some of these companies have successfully created an Indian image over the yearsThis study focusses on different attributes that contribute towards the buying behavior of consumers while mainly focusing on patriotism. Study also aims to check whether rural and urban consumers are indifferent towards such attitude.Study focuses on consumers of fast-moving consumer goods in Kozhikode district which is split into urban and rural areas and collecting data through convenient sampling method and the the sample size is 150.